Firearms: the leading cause of years of potential life lost - Peter Rhee; Rifat Latifi; Kartik Prabhakaran; Joshua Klein (Trauma Surgery & Acute Care Open)
Objectives Data from the Centers for Disease Control and Prevention (CDC) show that firearm deaths are increasing in the USA. The aims of this study were to determine the magnitude of potential years of life lost due to firearms and to examine the evolution of firearm deaths on the basis of sex, race, and geographical location within the USA.Methods Data was extracted (2009–2018) from the National Vital Statistics Reports from the CDC and the Web-based Injury Statistics Query and Reporting System database. Years of potential life lost was calculated by the CDC standard of subtracting the age at death from the standard year of 80, and then summing the individual years of potential life lost (YPLL) across each cause of death.Results The YPLL in 2017 and 2018 was higher for firearms than motor vehicle crashes (MVCs). In 2018, the YPLL for firearms was 1.42 million and 1.34 million for MVC. Males comprised the majority (85.4%) of the 38 929 firearm deaths. White males had the most YPLL due to suicide, with 4.95 million YPLL during the course of the 10-year period; black males had the most YPLL due to homicide with 3.2 million YPLL during the same time period. The largest number of suicides by firearms was in older white males. Firearm-related injury deaths were highest in the South, followed by the West, Midwest, and Northeast, respectively.Conclusion Firearms are now the leading cause of YPLL in trauma. Firearm deaths have overtaken MVC as the mechanism for the main cause of potential years of life lost since 2017. Suicide in white males accounts for more YPLL than homicides. Deaths related to firearms are potentially preventable causes of death and prevention efforts should be redirected.Level of evidence Level III—Descriptive Study.